FEASIBILITY TEST OF ICARE-BASED STUDENT ACTIVITY SHEETS (LKPD) ON NEWTON'S LAW MATERIAL - Tarigan, Ivana Angelia; Sinuraya, Jurubahasa (UNIVERSITAS NEGERI MEDAN, 2024)
This study aims to find out how the feasibility of ICARE-based LKPD and teacher and student responses to ICARE-based LKPD developed on Newton's Law material. This study used the Research and Development (R&D) method with a 4-D model modified by Thiagarajan et al (1974) by limiting the procedure to 3D due to limited research time. The results of the study show that in developing ICARE-based worksheets, knowledge of ICARE understanding and development models is required, which in this study uses 3D models.The feasibility of Student Worksheets (LKPD) after going through the validation and revision stages by media experts, material experts, teachers and students in this study was 82.65% which was included in the very feasible category and the response of teachers and students to ICARE-based physics LKPD in In this study, a percentage of 85.05% was obtained, where this value was included in the very feasible category so that it was proven that the developed ICARE-based Student Worksheets (LKPD) had met the eligibility to be used in physics learning on Newton's Law material in class X. Based on the results From this it can be concluded that the ICARE-based LKPD has met the eligibility to be used in learning Newton's Law material for class X high school students.